Directions of the development of single-family housing in Poland compared to the European trends - Przesmycka, Natalia (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
For more than twenty years, single-family housing in Poland is a booming sector of economy, as well as the main factor influencing the changes in cultural landscape of suburban and rural areas. The article presents Polish housing situation on the background of the EU countries in the aspect approaches to designing of new buildings.